Bridging the Gap between Digital Transformation and ESG in Insurance Firms - Janssen, Lisa (My University, 2023)
Abstract: Both digital transformation and ESG (Environmental, Social, Governance) objectives are mainstream, yet critical to today's economy. Multiple studies argue that there is a connection between digital transformation and ESG within the business context, but what that connection precisely entails remains a black box. The insurance industry is lagging in both digital transformation and ESG, so it could be assumed that insurance firms also lag in the possible connection. Several important factors were discovered by conducting an extensive literature review, several semi-structured interviews with experts in the field of insurance, and a validating document analysis. There seems to be no direct influence between digital transformation and ESG if this is not included in the organization’s business strategy. To have the most significant possible impact on ESG objectives after a digital transformation, a practical roadmap has been designed as a support for insurance firms, where the first step is to include ESG objectives into the business strategy, then to change the organizational structure and company culture, to lastly be able to make more sustainable decisions and to invest in a greener IT infrastructure.
Keywords: Digital Transformation, ESG, Sustainability, Insurance, Green Investments, Sustainable Investments